2021
DOI: 10.1055/a-1673-0280
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation Fragments in Cervicovaginal Fluid Are Associated with Intra-Amniotic Infection/Inflammation and Spontaneous Preterm Birth in Women with Preterm Premature Rupture of Membranes

Abstract: Objective: We sought to determine whether the levels of complement and other inflammatory and angiogenic mediators in cervicovaginal fluid (CVF) are independently associated with intra-amniotic infection and/or inflammation (IAI) and imminent spontaneous preterm birth (SPTB, ≤48 hours of sampling) in women with preterm premature rupture of membranes (PPROM). Study design: This was a retrospective study consisting of 85 singleton pregnant women with PPROM at 20+0 to 33+6 weeks. Amniotic fluid (AF) obtained via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…Nevertheless, there is a paucity of data regarding M‐CSF and inflammatory/infectious changes concerning preterm birth. Recent studies from our group have demonstrated that elevated M‐CSF levels in the CVF are independently associated with IAI in pregnancies complicated by PPROM and MIAC in women presenting with preterm labor 23,57 . Similarly, in the present study, we found that elevated CVF levels of M‐CSF are associated with microbial‐associated HCA (but not acute HCA), as well as acute HCA severity (Table S2).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Nevertheless, there is a paucity of data regarding M‐CSF and inflammatory/infectious changes concerning preterm birth. Recent studies from our group have demonstrated that elevated M‐CSF levels in the CVF are independently associated with IAI in pregnancies complicated by PPROM and MIAC in women presenting with preterm labor 23,57 . Similarly, in the present study, we found that elevated CVF levels of M‐CSF are associated with microbial‐associated HCA (but not acute HCA), as well as acute HCA severity (Table S2).…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies from our group have demonstrated that elevated M-CSF levels in the CVF are independently associated with IAI in pregnancies complicated by PPROM and MIAC in women presenting with preterm labor. 23,57 Similarly, in the present study, we found that elevated CVF levels of M-CSF are associated with microbialassociated HCA (but not acute HCA), as well as acute HCA severity (Table S2). However, further studies are needed to clarify the underlying mechanism and role of M-CSF in the CVF compartment associated with inflammation in the placenta and its relationship to infection in the amniotic cavity during pregnancy.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations